2003
DOI: 10.1063/1.1615765
|View full text |Cite
|
Sign up to set email alerts
|

Fisher information in density functional theory

Abstract: The Euler equation of the density functional theory is derived from the principle of minimum Fisher information. Both time-independent and time-dependent cases are analyzed. It is shown that Fisher information is a measure of the quality of the approximate density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 32 publications
1
68
0
1
Order By: Relevance
“…For various applications of the Fisher information in physics and chemistry see e.g. (Chakrabarty, 2004;Hornyák & Nagy, 2007;Nagy, 2003;2006;2007;Nagy & Liu, 2008;Nagy & Sen, 2006;Romera & Nagy, 2008;Szabó et al, 2008). We start with normalization condition (5) for the probability density ρ in which we perform integration by parts…”
Section: Fisher Informationmentioning
confidence: 99%
“…For various applications of the Fisher information in physics and chemistry see e.g. (Chakrabarty, 2004;Hornyák & Nagy, 2007;Nagy, 2003;2006;2007;Nagy & Liu, 2008;Nagy & Sen, 2006;Romera & Nagy, 2008;Szabó et al, 2008). We start with normalization condition (5) for the probability density ρ in which we perform integration by parts…”
Section: Fisher Informationmentioning
confidence: 99%
“…Let us finally remark that this quantity has been used (i) to describe, a factor apart, various macroscopic quantities, e.g. the kinetic [33,41,43,50] and Weissäcker [40,41,43], (ii) to derive the Schrödinger and Klein-Gordon equations of motion [24,39] as well as the Euler equation of the density functional theory [35] from the principle of minimum Fisher information, (iii) to predict the most distinctive non-linear phenomena (avoided crossings) encountered in atoms and molecules under strong external fields [26], and (iv) to measure the non-classicality of quantum systems [28,29], and (v) to obtain the foundations of thermodynamics in a microscopic way [25,37].…”
Section: The Fisher Informationmentioning
confidence: 99%
“…6,[9][10][11][12][13] In the next sections, we report the main aspects of the procedure in order to introduce the reader to the new conceptual and numerical aspects and we then show results for the nearly uniform electron gas. Appendix A reports relevant technical aspects of the MC calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the kinetic-energy functional could be written as the sum of two terms from information theory. 4 One term resembles the Fisher information 5,6 ͑analytical result͒, which is a measure of localization. The other term resembles the Shannon entropy 7 ͑numerical result͒, which is a measure of delocalization.…”
Section: Introductionmentioning
confidence: 99%